Perancangan Sistem Informasi Pemasaran Perumahan Berbasis Web - Julia Dwi Saputri; Ariansyah; Fajriyah (BETRIK, 2026)
Muara  Cipta  Baru  Housing  is  currently  still  conducting  marketing  manually  through  the  distribution  of  brochures  and  word-of-mouth,  resulting  in  limited  marketing  reach  and  less  effective  information  delivery.  To  improve  information  dissemination  and  make  things  simpler  for  prospective  buyers  to  acquire  data  regarding  house  types,  prices,  and  locations,  a  marketing  system  of  information  that  is  accesible  widely  and  quickly  is  required.  This  study  attempts  for  create  a  web-based  on  housing  advertising  system of information  utilizing  the  prototype  technique,  which  allows  the  system  development  process  to  be  carried  out  interactively  through  stages  of  requirement  communication,  rapid  design,  user  evaluation,  and  iterative  improvements  until  a  system  that  meets  needs  is  prodused.